A Clinical Study of Interception of Fistulous Tract with Application of Kshar Sutra (IFTAK)Technique Using Madhu Saindhav Aragwadhadi Kshar Sutra in the Management of Bhagandara (Crypto Glandular Fistula). - Sharma, Mohan Swarup; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2022)
The humanity had been suffered from various diseases and among the many uncomfortable conditions from the onset of civilization. Fistula in ano one of the most important one. Its anatomical situation makes it difficult to treat. It is known as Bhagandara in Ayurvedic classics. The disease was widely prevalent and numerous techniques were tried for its management. However, none of them could provide solace to the suffering mankind. Though there has been a lot of advancement in the modern surgery in recent years and many surgical diseases are treated with less invasive procedure such as laparoscopic and robotic surgeries which has revolutionized the management of surgical diseases. But fistula in ano is still the disease with high recurrence rates in present time also. Ayurveda offers an effective, safe, less invasive treatment modality called ksharsutra therapy which have been in since many centuries practice). Ksharsutra therapy has many advantages like the tract is completely excised by lekhan and improved healing simultaneously so, there are least chances of recurrence, minimal scaring and no chance of anal incontinence but Ksharsutra cause certain discomfort such as long anxiety period, number of hospital visit, Discomfort and longer duration of treatment. The present study regarding interception of fistulous tract with application of ksharsutra (IFTAK) was done in the patient of usually horse shoe type fistula, supralevator fistula, transsphinctor fistula, extra sphincter, fistula in ano which showed great potential in the management of fistula in ano by reducing the duration of treatment with minimal post operative scar.